Behavior of Different Ferrocement Structural Elements under Different Condition of Loading: Review (Iraqi Journal of Civil Engineering, 2021)
This study introduce a review on structural behavior of different structural elements such as beams, slabs, column….etc, under different type of loading. Through this review one can see the effectiveness of using ferrocement in casing slabs, beams subjecting to bending or impact load. Also the ferrocement make an essential role in strengthening of damage columns and beams.